A Systematic Review on Novel Mycobacterium tuberculosis Antigens and Their Discriminatory Potential for the Diagnosis of Latent and Active Tuberculosis - Meier, Noëmi R.; Jacobsen, Marc; Ottenhoff, Tom H. M.; Ritz, Nicole (Frontiers in Immunology, 2018)
Abstract Background: Current immunodiagnostic tests for tuberculosis (TB) are based on the detection of an immune response towards mycobacterial antigens injected into the skin or following an in-vitro simulation in interferon-gamma release assays. Both tests have limited sensitivity and are unable to differentiate different stages of latent tuberculosis infection (LTBI) and active tuberculosis disease (aTB). To overcome this, the use of novel Mycobacterium tuberculosis stage-specific antigens for the diagnosis of LTBI and aTB has gained interest in recent years. This review summarizes current evidence on novel antigens used for the immunodiagnostic of tuberculosis. Methods: A systematic literature review was performed in Pubmed, EMBASE and web of science searching articles from 2000 up until December 2017. Only articles reporting studies in humans using novel antigens were included. Results: Of 1533 articles screened 34 were included in the final analysis. A wide range of novel antigens expressed during different stages and types of LTBI and aTB have been assessed. M. tuberculosis antigens Rv0081, Rv1733c, Rv1737c, Rv2029c, Rv2031 and Rv2628, all encoded by the dormancy of survival regulon, were among the most widely studied antigens and showed the most promising results. These antigens have been shown to have best potential for differentiating LTBI from aTB. In addition, several studies have shown that the inclusion of cytokines other than interferon (IFN)-γ can improve sensitivity. Conclusion: There is evidence that the inclusion of novel antigens as well as the measurement of other biomarkers than IFN-γ can improve sensitivity and the discriminatory potential for the diagnosis of LTBI and aTB.